2008
DOI: 10.1016/j.bbrc.2008.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 associates with Rictor and is required for mTORC2 formation and activity

Abstract: mTORC2 is a multiprotein kinase composed of mTOR, mLST8, PRR5, mSIN1 and Rictor. The complex is insensitive to rapamycin and has demonstrated functions controlling cell growth, motility, invasion and cytoskeletal assembly. mTORC2 is the major hydrophobic domain kinase which renders Akt fully active via phosphorylation on serine 473. We isolated Hsp70 as a putative Rictor interacting protein in a yeast two-hybrid assay and confirmed this interaction via co-immunoprecipitation and colocalization experiments. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 34 publications
1
48
0
3
Order By: Relevance
“…The expression of Hsp70 is significantly associated with the amount of ATP in cells. The expression of Hsp70 is inhibited by the high levels of ATP; however, ATP depletion markedly induced the expression of Hsp70 (Arispe et al 2002;Martin et al 2008). Simmons et al (2005) and Selak et al (2003) have confirmed that mitochondrial ATP production was impaired in islets and muscle of IUGR rat, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…The expression of Hsp70 is significantly associated with the amount of ATP in cells. The expression of Hsp70 is inhibited by the high levels of ATP; however, ATP depletion markedly induced the expression of Hsp70 (Arispe et al 2002;Martin et al 2008). Simmons et al (2005) and Selak et al (2003) have confirmed that mitochondrial ATP production was impaired in islets and muscle of IUGR rat, respectively.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, it has been shown that Hsp72 is identified as a rictorbinding protein and a component of the mammalian target of rapamycin complex 2. 24 Activation of mammalian target of rapamycin complex 2, which consists of rictor, leads to the phosphorylation of Akt at Ser473, resulting in full activation of Akt. 25 Thus, the observation that Hsp70s regulate kinase function is not unique.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 family proteins are highly conserved and have three regions mediating interaction with various proteins, including an ATPase domain in the N-terminal region, a peptide binding domain in the C-terminal region, and an acidic motif (EEVD) at the C terminus. The peptide binding domain of Hsp70 has been reported to bind to PKC␤II, p53, Rictor, apoptosis-inducing factor (AIF), JNK1, TRAF2, TRAF6, Ku70, and MstI (7,11,16,29,37,40,54,58,59). Meanwhile, Hsp70 interacts with Hip, Bag-1, Bax, hYVH1, PARP-1, CD40, and Ask1 via its ATPase domain (3,17,25,26,36,53,64) and with Hop (Hsp70/Hsp90-organizing protein) and CHIP via the EEVD motif (1,12).…”
Section: Discussionmentioning
confidence: 99%